Organization of the educational process in the context of credit technology training - Balabekov, K.N.; Zhalgasbekova, Z.K. (KSU Publ., 2017)
This article is devoted to the forms of organization of independent work of students in credit technology of education. Independent work takes at least 50 % of the school time and its organization is an actual problem. At present, it is impossible to name the area of human activity in which the methods of using information technologies would not be used. This is an effective means of cognizing the use of information technology. The traditional form of the organization of studies is completely obsolete with the credit technology of training. The main way of information transfer is one-way communication: the teacher translates knowledge, and the learner reproduces them.The main source of education is the experience of the teacher. Sometimes there is a two-way communication: a lecture, a teacher, a student, or a seminar, a student, a teacher. One-way communication is justified only in the event of a lack of information, the impossibility of receiving it in a different way, except from the lecturer's story. The way out of this situation is the organization of multilateral communication. When organizing the training in the form of multilateral communication, the following advantages over the traditional are achieved: the activity of all participants in the process, parity, the absence of repressive management and control measures, and the introduction of the learner's knowledge into the educational process. The article briefly describes the main forms of this work, as well as lists the forms of organization of independent work using information technology.
Кредиттік оқыту технологиясы аясында оқу процесін ұйымдастыру түрлері
Организация учебного процесса в условиях кредитной технологии обучения
Keywords: glossary training; written creative works; methods of rational reading; control exercises; IP-helping; logically closed blocks; modules; logical schema of the knowledge base; terminological dictionaries; written creative work; study of literature on the topic of the essay; essay; TV essay; teletheutoring; Testtraining; electronic benefit